A review of the role of HEI's in developing academic entrepreneurship: An evaluative study of Uttarakhand state, India. Issue 2 (1st June 2015) - Sharma, Lalit
Abstract : Purpose: – The prime purpose of the study is to assess the role of education in general and entrepreneurship education in particular in developing youth entrepreneurship in Uttarakhand State, India. The study also tested the methodology based on effectiveness and compared it with the traditional ex post method to find if there is any difference in results. Alternatively, the study also checked whether the students of developing economies are more likely to take up entrepreneurship as a career, which has strongly been contended by some of the recent studies. Design/methodology/approach: – The role of education was assessed on two grounds: increase in general awareness and knowledge about entrepreneurship, and development of entrepreneurial intentions and inclination of students. A structured questionnaire was administered on 530 final-year students. The questionnaire tested the interest and intentions of students towards taking up entrepreneurship as a career and also evaluated the level of awareness and knowledge of entrepreneurship among the students. Cross-tabulation, mean values and t -test were used to analyse the results. Findings: – The research confirmed that higher education institutions (HEIs) of Uttarakhand have not been very effective in building entrepreneurial awareness and knowledge level of students. Students who studied entrepreneurship subject showed a little better awareness and knowledge level of entrepreneurship, which was found to be statistically significant in comparison to their counterparts, but the mean scores indicated poor knowledge level. As the authors used an ex post method and method based on effectiveness of entrepreneurship education, the authors got two different results for impact of entrepreneurship education on entrepreneurial intentions. More appropriate one being that with the observed level of awareness and knowledge level of entrepreneurship (which was very low); the authors cannot possibly determine the actual impact of entrepreneurial education on entrepreneurial intentions. Practical implications: – The research has direct implications for research scholars working in the field of determining the impact of entrepreneurship education on entrepreneurial intentions, entrepreneurship education institutions and also the policymakers. Originality/value: – In comparison to most of the earlier studies done to find the impact of entrepreneurship education on entrepreneurial intentions, this study differs in its methodological approach and first of all evaluates the effectiveness and impact of entrepreneurial education in developing entrepreneurial awareness and knowledge of student. The author undertakes that if entrepreneurship education is ineffective in developing the desired level of awareness and knowledge of entrepreneurship, the actual effect of entrepreneurial education on entrepreneurial intentions cannot actually be determined and the authors may not be able to get accurate outcomes of such studies. To justify the stand, author compares the traditional ex post approach with the approach based on effectiveness of the programme and brings into light the difference in outcomes. The proposed approach rests on the premises that education must be absorbed and not just delivered to assess its impact.